Mesenchymal stem cells elicits Anti-PD1 immunotherapy by targeted delivery of CX3CL1 - Liu, Jize; Ma, Xiaomin; Liu, Chuxuan; Cheng, Yang; Li, Bingjun; Zhang, Wenjie; Zeng, Runzhi; Chen, Qishuai; Zhang, Yun; Hu, Sanyuan (Frontiers in Pharmacology, 2023)
Anti-PD1/PDL1 monotherapy has failed to acquire sufficiently ideal results in most solid tumors. Mesenchymal stem cells (MSCs) have been reported to exert therapeutic effects on some tumors, but the functions of MSCs in colorectal cancer (CRC) need further research. In this study, we aimed to investigate the therapeutic effect and the improvement of sensitivity of MSCs to anti-PD1 antibodies (αPD1) in CRC and to evaluate the possible mechanism. The relative distribution of immune cells in tumor microenvironment was examined after the mice were treated with MSC and/or αPD1. Our study revealed that MSC recruits CX3CR1high macrophages and promotes M1 polarization to inhibit tumor growth via highly secretion of CX3CL1.The combination of MSC and αPD1 was superior to monotherapy against CRC. MSC inhibits PD1 expression on CD8+ T cells by facilitating M1 macrophage polarization, which promotes the proliferation of CD8+ T cells, thus improving the sensitivity to αPD1 therapy in CRC. Additionally, the above therapeutic effect disappeared after inhibiting the secretion of CX3CL1 in MSC. Our MSC-based immunotherapeutic strategy simultaneously recruited and activated immune effector cells at the tumor site, suggesting that the combination of MSC and αPD1 could be a potential therapy for CRC.